Hikayat Seri Rama: Establishing the source - Rajantheran, Muniandy; Maniam, Krishanan; Kandasamy, Silllalee S.; Samuel, Samikkanu Jabamoney Ishak (Primrose Hall Publishing Group, 2019)
Purpose of the study: The main aim of this paper is to establish the Tamil literary sources of the Hikayat Seri Rama. Various recensions of the Hikayat Seri Rama demonstrate the close identity between one text and the other which would seem to indicate that all these texts were apparently derived from some older versions of the Rama story, which was the common source of all the recensions. Methodology: The methodology employed in this article is qualitative in nature. It is library research based on the existing published materials. Four steps of Hermeneutics approaches have been employed to produce findings which are objective in nature. This research is aimed to contribute to the existing body of knowledge about the sources of Hikayat Seri Rama. Main findings: This study would enable us to appreciate the close similarity of motifs and episodes between HSR and the Rama story in Tamil tradition. The Rama story in Tamil folklore itself stands out as a great proof to manifest that the Tamil sources are predominant in Hikayat Seri Rama compared to any other sources. Applications of this study: This study will contribute to the existing body of knowledge and will enable one to appreciate the close cultural relationship between the Tamil and the Malay literary traditions. Hence, it provides a platform for the positive cultural as well as civilizational dialog between the two communities. Additionally, this article can also contribute to the comparative studies involving Indian and Malay literature. Novelty/Originality of this study: Literature reviews clearly show that there is no other similar study to this work conducted elsewhere. Hence, the originality of this study is established. Previous studies failed establish the source for the Hikayat Seri Rama as most of those studies ignored Tamil literary sources. This study managed to prove the source of Hikayat Seri Rama based on Tamil literary sources.. © 2019 Primrose Hall Publishing Group.